2021
DOI: 10.3126/mjsbh.v20i2.30309
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practice of Junk Foods among Adolescents in Secondary Level Students

Abstract: Introduction: Junk food consumption among adolescents has become a serious issue that may lead to harmful effects on health. Dietary patterns of people are shifting from homemade foods to junk foods. Therefore, this study was undertaken to assess the awareness and practice of junk foods among adolescents. Methods: A descriptive cross-sectional study was conducted among adolescents of secondary level students. A simple random sampling technique was used to select the sample and the sample size was 237. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…27 This consistency might be the outcome of similar mindset of adolescents towards the processed foods. Level of knowledge was not found to be associated with the practice of sugary foods and drinks which is consistent with the findings of another study conducted in schools of Kathmandu by Paudel et al 30…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…27 This consistency might be the outcome of similar mindset of adolescents towards the processed foods. Level of knowledge was not found to be associated with the practice of sugary foods and drinks which is consistent with the findings of another study conducted in schools of Kathmandu by Paudel et al 30…”
Section: Discussionsupporting
confidence: 90%
“…27 The yields in this study were higher compared to those of other studies conducted by Upreti et al and Subedi et al in Chitwan where the adequate knowledge among adolescents were found to be 55.9% and 65.6% respectively. 28,29 However, this finding accord with another study done by Paudel et al 30 indicating higher number of respondents with adequate knowledge regarding health effects of processed foods including sugary items among comparable population which is obvious due to similarity in population and study settings. The finding is contrary to previous studies conducted in surrounding neighboring nations including India 31 , Vietnam and Thailand 32 with similar context where low level of adequate knowledge was seen among adolescents regarding processed foods and sugary beverages.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[19] A statistically significant association was found between insufficient physical activity and the unavailability of playing space. [15,16,20,21] It could be said that there might be various reasons for students not being physically active enough, and could include reasons like lack of designated space to play or safety of the place, academic pressure, lack of enough time to carry out such activities, etc.…”
Section: Discussionmentioning
confidence: 99%